2018
DOI: 10.1002/biot.201700543
|View full text |Cite
|
Sign up to set email alerts
|

EasyCloneYALI: CRISPR/Cas9‐Based Synthetic Toolbox for Engineering of the Yeast Yarrowia lipolytica

Abstract: The oleaginous yeast Yarrowia lipolytica is an emerging host for production of fatty acid-derived chemicals. To enable rapid iterative metabolic engineering of this yeast, there is a need for well-characterized genetic parts and convenient and reliable methods for their incorporation into yeast. Here, the EasyCloneYALI genetic toolbox, which allows streamlined strain construction with high genome editing efficiencies in Y. lipolytica via the CRISPR/Cas9 technology is presented. The toolbox allows marker-free i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
199
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(223 citation statements)
references
References 28 publications
1
199
0
Order By: Relevance
“…Our previous work has shown that it is difficult to express heterologous genes in C. tropicalis , so codon optimization of the entire gene would be the best way forward (L. Zhang et al, ). Using either the monocistronic or polycistronic transcript version, the efficiency of double gene deletion in C. tropicalis was lower than that in S. cerevisiae (Y. P. Zhang et al, ) and industrial yeast (Lian et al, ), but higher than that in Yarrowia lipolytica (Holkenbrink et al, ). Part of the reason for this lack of efficiency may be that the “HH‐N20 target sequence‐sgRNA scaffold‐HDV” construction is not the most suitable for multiple RNA processing in C. tropicalis .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has shown that it is difficult to express heterologous genes in C. tropicalis , so codon optimization of the entire gene would be the best way forward (L. Zhang et al, ). Using either the monocistronic or polycistronic transcript version, the efficiency of double gene deletion in C. tropicalis was lower than that in S. cerevisiae (Y. P. Zhang et al, ) and industrial yeast (Lian et al, ), but higher than that in Yarrowia lipolytica (Holkenbrink et al, ). Part of the reason for this lack of efficiency may be that the “HH‐N20 target sequence‐sgRNA scaffold‐HDV” construction is not the most suitable for multiple RNA processing in C. tropicalis .…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Holkenbrink et al . () developed a toolkit based on an alternative USER cloning approach, which allows the integration of one to two TUs at intergenic regions called EasyCloneYALI. The system largely utilizes a ku70 mutant background and a CRISPR/Cas9 strategy, and it carries out improved homologous recombination at specific non‐coding loci.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, with a one-pot reaction, we are able to assemble three TUs, a marker and various integration site sequences, which correspond to the assembly of twelve fragments in a destination vector. Very recently, Holkenbrink et al (2018) developed a toolkit based on an alternative USER cloning approach, which allows the integration of one to two TUs at intergenic regions called EasyCloneYALI. The system largely utilizes a ku70 mutant background and a CRISPR/Cas9 strategy, and it carries out improved homologous recombination at specific non-coding loci.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology combined with the multigene overexpression system for heterologous genes (Ledesma-Amaro et al, 2018) will allow to avoid the use of selectable markers for metabolic engineering applications in A. gossypii. Similar toolkits have been described in other biotechnological microorganisms such as Yarrowia lypolytica, thus enabling the rapid engineering of metabolic pathways in that oleaginous yeast (Wong et al, 2017;Holkenbrink et al, 2018;Larroude et al, 2018).…”
Section: Introduction Of Point Mutations Using the Crispr/cas9 Systemmentioning
confidence: 98%